Review of Chemical, Biological, and Epistemological Elements: Mamaq Tradition - Nora Listantia; Muhammad Sarjan (Postgraduate, University of Mataram, 2023)
Mamaq by the ancestors of the Sasak people was an activity of chewing betel nut, lime, betel leaf, and tobacco, and ending with shrinkage. Betel leaves contain glycosides, steroids, triterpenoids, flavonoids, tannins, and anthraquinones. These compounds contain antimicrobial activity that can fight Staphylococcus aureus, Escherichia coli, and Candida albicans fungi. Meanwhile, whiting is a strong base because it has a pH of 11-12.5. This is because in the mouth there is saliva which can maintain a pH of around 6.8. Saliva contains phosphate buffer solutions H2PO4- and HPO42-. And gambir contains a component in the form of catechins which function as antioxidants and antibacterials. The purpose of this research is to study philosophical values, especially epistemology, which investigates the origin, and composition of methods and knowledge related to mamaq philosophy and natural science concepts, especially chemistry, and compounds, and what reactions occur in the mamaq process that has not been revealed. The study uses the library method. From the results of thestudy, it was concluded that in addition to the philosophy in the ingredients for mamaq it can also be described the chemical compounds contained in the ingredients for mamaq, starting from whiting, green betel leaf, gambier, and areca nut.